Age at first drink and severity of alcohol dependence - Chatterjee, K. (Med J Armed Forces India, 2021)
BACKGROUND: Early age at first drink (AFD) has been linked to early onset and increased severity of alcohol dependence in various studies. Few Indian studies on AFD have shown a negative correlation between AFD and severity of alcohol dependence. Our study aimed to explore this relationship in patients with alcohol dependence syndrome (ADS) diagnosed using ICD-10 criteria. METHODS: One hundred fifty-one consecutive patients freshly diagnosed with ADS were included in the study, which was conducted at the psychiatry unit of a tertiary care, multispecialty hospital. The Addiction Severity Index (ASI) was used to assess severity of alcohol dependence. RESULTS: Mean AFD was 24.85 years (range = 13–40 years). Median ASI score was 36 (range = 21 to 57). The study yielded a weak negative correlation (ρ = −.105) between AFD and ASI, which was statistically not significant. CONCLUSIONS: We found no correlation between AFD and severity of alcohol dependence at detection in Indian Armed Forces personnel, which is contrary to what has been reported worldwide and in previous Indian studies. Delayed initiation of alcohol use among those enrolling in the Indian Armed Forces and early detection of alcohol dependence within the military environment are possible explanations.